Keabsahan Keputusan Perusahaan dalam Hal Direksi yang Mengambil Keputusan Masa Jabatannya Sudah Selesai Berdasarkan Akta Perubahan Anggaran Dasar Terakhir - Ariatna, Salsabila; Widyawati, Sri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The Board of Directors has the authority to manage the company. In carrying out management, the Board of Directors has the authority based on the Deed through the General Meeting of Shareholders whose term of office is determined in the Articles of Association of PT. The problem is that the Board of Directors whose term of office has ended but still carries out their duties and functions. The research method used in this writing is the normative juridical method. From the results of this research, it is concluded that the company's decision in the event that the Board of Directors makes a decision whose term of office has expired, then the decision is invalid unless all actions and decisions of the Board of Directors since the expiration of the term of office have been recognized and considered as the responsibility of the company by the decision of the shareholders in the GMS forum. Directors who carry out management outside their term of office are invalid but can be said to be valid if there is ratification of decisions made by Directors whose term of office has ended. The legal consequence of decision-making by unauthorized directors is that the directors are not responsible for their personal assets.